DIAGNOSES AND NURSING INTERVENTIONS IN AN ACCIDENT AND EMERGENCY UNIT IN THE LIGHT OF BASIC HUMAN NECESSITIES - Leni de Lima Santana; Verônica de Azevedo Mazza; Samanta Andrine Marschall Taube; Leila Maria Mansano Sarquis (Universidade Federal do Paraná, 2011)
This exploratory, retrospective documental research was undertaken in a Medical Emergency Center in Curitiba, Paraná, Brazil. The study's objectives were to identify the most frequent Basic Human Needs in hospitalized adult patients and to list the diagnoses and nursing interventions necessary to attend the affected needs. ICNP® Version 1, the ICNPCH (International Classification of Nursing Practice - Community Health) Project and Wanda Horta's theory of Basic Human Needs were used as a base. Data collection took place through analysis of 512 documents which made up the patients' medical notes. The situations identified were classified into sixteen psycho-biological need and one psychosocial need. For the situations to be attended, 214 diagnoses were made and 308 nursing interventions. The identification of the needs, and the elaboration of care plans coherent with reality, were indispensable for the achievement of care goals, the Nursing Process being the facilitating tool for the Nursing work.